How Fragile a Tradition? The Bournonville Festival - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2005)
The Bournonville Festival. PALABRAS CLAVE: Bournonville Festival, aniversary, Royal Danish Ballet.
Dentro del apartado "August Bournonville. The Royal Danish Ballet hosts a birthday celebration".